2012
DOI: 10.1371/journal.pone.0052493
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Lactobacillus rhamnosus CNCM I-3690 Strain Protects against Oxidative Stress and Increases Lifespan in Caenorhabditis elegans

Abstract: Numerous studies have shown that resistance to oxidative stress is crucial to stay healthy and to reduce the adverse effects of aging. Accordingly, nutritional interventions using antioxidant food-grade compounds or food products are currently an interesting option to help improve health and quality of life in the elderly. Live lactic acid bacteria (LAB) administered in food, such as probiotics, may be good antioxidant candidates. Nevertheless, information about LAB-induced oxidative stress protection is scarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(169 citation statements)
references
References 65 publications
11
136
2
3
Order By: Relevance
“…We hypothesize that the increased survival of these animals might be related to a more efficient reduction of ROS in the presence of both enzymes (CAT and SOD), conferring a higher antioxidant protection. Moreover, in a recent study it has been shown that an anti-inflammatory strain of L. rhamnosus CNCMI-3690 protected against oxidative stress and increased the life span in Caenorhabditis elegans through a differential expression of the DAF-16/insulin-like pathway (28). It is also important to note that in both protocols of administration, WT S. thermophilus CRL 807 also decreased the severity of the inflammation compared to that in the TNBS control group, corroborating the innate antiinflammatory potential of this strain selected by in vitro and in vivo assays.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the increased survival of these animals might be related to a more efficient reduction of ROS in the presence of both enzymes (CAT and SOD), conferring a higher antioxidant protection. Moreover, in a recent study it has been shown that an anti-inflammatory strain of L. rhamnosus CNCMI-3690 protected against oxidative stress and increased the life span in Caenorhabditis elegans through a differential expression of the DAF-16/insulin-like pathway (28). It is also important to note that in both protocols of administration, WT S. thermophilus CRL 807 also decreased the severity of the inflammation compared to that in the TNBS control group, corroborating the innate antiinflammatory potential of this strain selected by in vitro and in vivo assays.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of C. elegans incubation media with a strain of lactic acid bacteria Lactobacillus rhamnosus CNCMI-3690, which exhibits antioxidant activity, increased lifespan and protected against oxidative stress. This strain of lactic acid producing bacteria also reduced inflammation [15]. These studies suggest that increased levels of antioxidants extend the lifespan by reducing oxidative stress and possibly by other mechanisms, such as preventing deregulation of protective transcriptional factors.…”
Section: Studies On C Elegans With Antioxidant Supplementationmentioning
confidence: 70%
“…The transcription factor FoxO1 has been related to the response of probiotics in C. elegans oxidative stress, skin acne and alcoholic fatty liver [22,45,46]. Nevertheless, this is the first study linking FoxO1 activation to probiotics response in intestinal mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous finding from our group demonstrated that FoxO1 homologous gene in C. elegans, daf-16, is involved in the protection exerted by probiotics from oxidative stress induced by H 2 O 2 in this organism [22]. Based on these findings, we wanted to explore if this transcription factor was also related to the oxidative stress response in mammalian cells.…”
Section: Activation Of Foxo1 In Response To Oxidative Stress and Tnfαmentioning
confidence: 99%
See 1 more Smart Citation